Telephone support for dementia family caregivers during the COVID‐19 pandemic: Experiential differences in spouse and adult‐child caregivers. (December 2021) - Lee, Jung‐Ah; Ju, Eunae; Tom, Courtney; Tran, Tiffany Marie
Abstract: Background: Due to the COVID‐19 pandemic, family caregivers stayed home with their person with dementia (PWD) continuously for 24/7. They faced limited social activity with lack of essential services such as adult daycare and in‐home services. Social restrictions can worsen cognitive deterioration and increase behavioral problems of PWD, causing increased caregiver burden, distress, and loneliness. Caregiver research team developed a telephone support intervention with trained university students who provided emotional support, and COVID‐19 information. The objective of the study is to identify the different needs in caring between spousal caregivers and adult‐child caregivers for community‐dwelling PWD during this pandemic. Methods: Family caregivers were recruited through our previous home‐visit family caregiver study. Trained bilingual university students conducted telephone support calls in English, Spanish, Korean or Vietnamese as preferred by caregiver participants, once a week during the 3 month of the early pandemic period. Students summarized each conversation in a call log for debriefing by a gerontology faculty. Thematic analysis using call logs was conducted and coded by two independent raters by using Dedoose, a qualitative data analysis tool. Similarities and differences between spousal caregivers and adult‐child caregivers were identified. Results: 14 spousal caregivers (11 were wives and 3 were husbands, mean age 67.4) and 11 adult‐child caregivers (daughters, mean age 49) participated in the study. Three themes were identified: (1) spousal caregivers had high sense of being left alone and isolated while adult‐child caregivers felt a greater responsibility for the family including PWD care, (2) both groups showed increased stress but for spouse caregivers it was due to worsening PWD behaviors, for adult‐child caregivers it was the restriction on social interaction and concerns about losing jobs, (3) similarities in adapting to the COVID‐19 safety recommendations and incorporating it into everyday life. Conclusion: The findings showed an increase in stress and anxiety in both groups but the differences were: for spouse high level of loneness, difficulty with PWD behaviors; for adult‐child caregivers greater burden due to family and reduced social life. Both groups followed COVID‐19 safety protocol and highly appreciated the telephone‐based emotional support during the pandemic.